Eco-Innovation, sustainability and business model innovation by open innovation dynamics - Magdalena Pichlak; Adam R. Szromek (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
The paper aims to analyze the environmental aspects of innovation activity undertaken by companies and, in particular, to assess sustainable business leaders' propensity to generate ecoinnovation. The research described in the paper was descriptive and, to some extent, diagnostic. It was based on a non-random sample and was conducted-using the Computer Assisted Telephone Interview (CATI) method-in 2019 among 54 of the most eco-innovative Polish companies. The results of the research indicate that they are more likely to generate radical rather than incremental changes. Moreover, the most eco-innovative companies are those developing technologies for biodiversity protection. The results further indicate that companies with more than 50 employees have a higher propensity to develop incremental and radical eco-innovation than smaller firms with relatively fewer resources. Finally, this study shows that adopting an open innovation strategy strengthens the propensity to generate eco-innovation, especially radical ones. Moreover, developing such changes is dominated by the adoption of strategic and operational forward supply chain collaboration, involving the absorption of knowledge and information streaming directly from the market. The results can provide a frame for developing new business models incorporating collaboration in eco-innovation activities, especially in the situation of a post-pandemic recovery of the economy.
Keywords: 650; sustainable business; environmental innovation; open innovation; open eco-innovation